Medium-Term Forecasts of Potential GDP and Inflation Using Age Structure Information - Thomas Lindh (Sveriges Riksbank, 1999)
Economic behavior as well as economic resources of individuals vary with age. Swedish time series show that the age structure of the population contains information correlated to medium-term trends in growth, inflation and other macroeconomic data. GDP gaps estimated by age structure regressions are closely related to conventional measures using filters, time series methods, and structural models. Reliable estimates of potential GDP and other macroeconomic series often become available after (at least) a one-year lag. Monetary policy is believed to affect inflation with a lag of one or two years. Projections of the populations age structure are comparatively reliable several years ahead and provide additional information to improve on 3-5 years-ahead forecasts of potential GDP and inflation.
Keywords: E31; E44; J10; O52; 330; Age structure; Inflation forecasts; Potential GDP